Understanding the association of individual pollutants with pneumonia episodes in children under five in Abuja, Nigeria - Adaji, Enemona (2021)
Background Pneumonia kills nearly one million children under the age of five globally, every year. Despite reductions in global pneumonia mortality, progress in the highest-burden countries remains slow. 60% of all pneumonia fatalities occur in 10 countries of which Nigeria is currently number one overtaking India. Equally, air pollution remains a major public health concern worldwide. Globally air pollution is responsible for over 7 million deaths annually. Exposure to high levels of pollution is constantly on the rise, especially in urban cities. Exposure to air pollution alters lung health in many ways leading to the exacerbation of respiratory illnesses. Consequently, this would increase the risk of developing pneumonia especially in vulnerable populations such as children where the respiratory tract is still underdeveloped.